Meta-Analysis: The Effectiveness of Using mHealth to Improve Antenatal Care - Kartikasari, Mayriyana; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: One of the innovations in technology in health that can be used is mHealth. The use of technology such as mHealth allows for the dissemination of information to pregnant women in an effort to improve antenatal care. This study aims to determine the effectiveness of using mHealth on antenatal care. Subjects and Method: This was a systematic review and meta-analysis study using PICO, Population: Pregnant women, Intervention: Using mHealth, Comparison: Not using mHealth/ standard services, Outcome: ANC visits. The articles used in this study came from 6 databases including Pubmed, ScienceDirect, Google Scholar, BMJ, Springer link, Sage, and Core. The keywords of the article are, Telemedicine OR Mobile Health OR Health Mobile OR Telehealth OR mHealth OR eHealth AND Short Message AND Quality Improvement OR Quality Improvement OR Quality Improvements OR Quality Improvements AND Prenatal Care OR Prenatal Care OR Antenatal Care OR Antenatal Care. The articles included in this study are complete articles, RCT study designs for 2012-2022. Results: There are 8 RCT articles from 3 continents, including Africa (Kenya, Ethiopia, Zanzibar), Asia (India), America (Peru, Brazil). It was found that using mHealth could increase ANC visits by 1.32 times compared to not using mHealth (RR=1.32; 95% CI=1.10 to 1.59; p=0.003). Conclusion: effective use of mHealth to improve antenatal care.